Enhancement in energy storage density of polyvinylidene fluoride composites by introduced rod-like core-shell Ag@Al2O3 nanorods. (18th July 2018) - Guan, Lizhu; Liu, Lizhu; Weng, Ling; Zhang, Xiaorui; Cui, Weiwei
Abstract: A typical core-shell structural silver@aluminum oxide (Ag@Al2 O3 ) nanorods was successfully synthesized by silver nitrate reduction method combined with hydrolysis of aluminum sulfate. The Ag@Al2 O3 core-shell nanorods were used as functional fillers to improve the dielectric properties of polyvinylidene fluoride (PVDF). The thermal, mechanical and dielectrical properties of PVDF based composites were characterized. A comparative study on the dielectric properties of PVDF based composites with the filler of Ag and Ag@Al2 O3 core-shell nanorods was also reported. Results showed that Al2 O3 could make a homogeneous shell out of the Ag nanorods, and the Ag@Al2 O3 core-shell nanorods also have a good dispersion in PVDF matrix. The Ag@Al2 O3 /PVDF composites with 15 wt% have a more superior expression on energy density (0.026023 J/cm 3 ) within a rather low dielectric loss (0.015) and leakage current density (4.41 E −8  A/cm 2 ), and the storage is 1.82 times higher than that of the pure PVDF. This improvement in energy storage of composites should be attributed to the occurrence of Al2 O3 shell which effectively prevented the leakage current and resulted the reducement in the dielectric loss of the composites. Graphical abstract: Image 1 Highlights: Al2 O3 was uniformly coated on the surface of Ag nanorods with approximately 35 nm in thickness. The addition of Ag@Al2 O3 nanorods could induce the transition of PVDF phase from α to β and γ. Ag@Al2 O3 nanorods improve the thermal stability and electrical storage properties of PVDF composites than Ag nanorods do. The Ag@Al2 O3 /PVDF composites show a better electrical storage capacity than Ag/PVDF composites.